IMPLEMENTASI LAUDATO SI' DARI PARA MAHASISWA BAGI LINGKUNGAN KAMPUS STIPAS KEUSKUPAN AGUNG KUPANG - Kuma Kleden , Permata Barbara; Un Bria , Florens Maxi; Abatan , Yofince (Pastoralia Jurnal Penelitian Dosen, 2024)
This research was motivated by the low level of student concern for environmental cleanliness on the STIPAS campus of the Kupang Archdiocese, which was characterized by the large amount of rubbish scattered around such as leaves, plastic, tissue and paper in the campus area. In response, this research uses guidance from Pope Francis' Encyclical Laudato Si' which emphasizes the importance of protecting the earth as a common home from damage caused by irresponsible human actions. The research method used is a qualitative approach, with data collection techniques through observation, interviews and literature review. Research informants consisted of STIPAS lecturers, staff and students. This research aims to understand the level of student concern for environmental cleanliness, supporting and inhibiting factors, as well as efforts that can be made to increase this concern based on the principles of Laudato Si'. The research results showed that the informants' environmental awareness increased after studying the concepts in Laudato Si'. Concrete actions such as waste management, energy savings, and participation in environmental activities have been taken. Implementation of Laudato Si' values ​​on campus also results in policy and behavioral changes, such as reducing waste and actively involving students in maintaining a clean environment. The conclusion of this research emphasizes the importance of implementing Laudato Si' values ​​to increase students' environmental awareness, with support from campus policies and cooperation from all parties.